2019
DOI: 10.3389/fneur.2019.00889
|View full text |Cite
|
Sign up to set email alerts
|

Small Vessels Are a Big Problem in Neurodegeneration and Neuroprotection

Abstract: The cerebral microcirculation holds a critical position to match the high metabolic demand by neuronal activity. Functionally, microcirculation is virtually inseparable from other nervous system cells under both physiological and pathological conditions. For successful bench-to-bedside translation of neuroprotection research, the role of microcirculation in acute and chronic neurodegenerative disorders appears to be under-recognized, which may have contributed to clinical trial failures with some neuroprotecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 284 publications
(322 reference statements)
1
46
0
Order By: Relevance
“…Recent studies have revealed the significance of capillary stalling in aging, stroke, Alzheimer's disease, polycythemia and thrombocythemia 3,4,5,6,11,21,22,23 . In fact, capillary stalling largely impacts on CBF, and cognitive functions can be improved by suppressing capillary stalling in Alzheimer's disease 6,24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have revealed the significance of capillary stalling in aging, stroke, Alzheimer's disease, polycythemia and thrombocythemia 3,4,5,6,11,21,22,23 . In fact, capillary stalling largely impacts on CBF, and cognitive functions can be improved by suppressing capillary stalling in Alzheimer's disease 6,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Further, we examined the consequence of increased capillary stalling. We considered that alterations in the microcirculation, such as due to stalling, would reduce the efficiency of oxygen delivery to tissues that are presumably associated with the SVaD pathogenesis 21,35 .…”
Section: Discussionmentioning
confidence: 99%
“…The cells have been variably called as ensheathing pericytes Grant et al, 2019), transition/transitional pericytes (Kisler et al, 2017a;Arango-Lievano et al, 2018), pre-capillary pericytes (Zimmermann, 1923), simply 'pericytes' or 'capillary pericytes' (Hall et al, 2014;Attwell et al, 2016;Cai et al, 2018;Khennouf et al, 2018;Grubb et al, 2020), smooth muscle-pericyte hybrids (Hartmann et al, 2015;Yang et al, 2017;Dalkara, 2019), arteriole SMC (aaSMC) (Vanlandewijck et al, 2018), or pre-capillary SMCs (Hill et al, 2015). At the same time, the vessels of proximal branches coming off penetrating arterioles are also differently defined as pre-capillary arterioles (Fernández-Klett et al, 2010;Hartmann et al, 2015;Hill et al, 2015;Berthiaume et al, 2018;Erdener and Dalkara, 2019;Grant et al, 2019), post-arteriole capillaries (Gould et al, 2016) or a part of capillaries (Hall et al, 2014;Attwell et al, 2016;Cai et al, 2018;Khennouf et al, 2018;Grubb et al, 2020).…”
Section: Pericytes In the Proximal Capillariesmentioning
confidence: 99%
“…Blood-brain barrier breakdown and microvessel dysfunction has been observed in various CNS disorders such as small vessel disease (SVD), ischemic acute stroke, intracerebral hemorrhage, Alzheimer's disease (AD), traumatic brain injury (TBI)/chronic traumatic encephalopathy (CTE), multiple sclerosis (MS), amyotrophic lateral sclerosis (ALS), Lewy body diseases (LBD), and epilepsy (Winkler et al, 2013;Coatti et al, 2019;Erdener and Dalkara, 2019;Geranmayeh et al, 2019). In particular, pericyte dysfunction is thought to be a critical factor for aggravating dementing diseases such as vascular cognitive impairment/dementia and AD (Sagare et al, 2013;Montagne et al, 2018;Nikolakopoulou et al, 2019).…”
Section: Pathological Roles Of Pericytes In Cerebrovascular Diseases mentioning
confidence: 99%
“…Neurological diseases such as ischemic stroke, traumatic brain injury, Alzheimer's Disease (AD), amyotrophic lateral sclerosis and Parkinson's disease are characterized by pericyte dysfunction [64]. Hereafter, short description of pericyte involvement in ischemia-reperfusion and brain tumor is presented.…”
Section: Pericytes In Brain Disease Repair and Preservationmentioning
confidence: 99%